Construction biotechnology : biogeochemistry, microbiology and biotechnology of construction materials and processes /: biogeochemistry, microbiology and biotechnology of construction materials and processes. ([2016]) - Ivanov, Volodymyr; Stabnikov, Viktor
No abstract available